2012
DOI: 10.2344/11-17.1
|View full text |Cite
|
Sign up to set email alerts
|

Demand in Pediatric Dentistry for Sedation and General Anesthesia by Dentist Anesthesiologists: A Survey of Directors of Dentist Anesthesiologist and Pediatric Dentistry Residencies

Abstract: This study describes what training programs in pediatric dentistry and dental anesthesiology are doing to meet future needs for deep sedation/general anesthesia services required for pediatric dentistry. Residency directors from 10 dental anesthesiology training programs in North America and 79 directors from pediatric dentistry training programs in North America were asked to answer an 18-item and 22-item online survey, respectively, through an online survey tool.The response rate for the10 anesthesiology tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 7 publications
1
19
1
4
Order By: Relevance
“…12 The results generated from this study support the use of fospropofol as an alternative to midazolam for IV moderate sedation during dental surgeries. Fospropofol, when administered by a dentist anesthesiologist, appears to confer some advantages over the traditionally used benzodiazepine, most notably producing a somewhat faster recovery time.…”
Section: Discussionsupporting
confidence: 50%
“…12 The results generated from this study support the use of fospropofol as an alternative to midazolam for IV moderate sedation during dental surgeries. Fospropofol, when administered by a dentist anesthesiologist, appears to confer some advantages over the traditionally used benzodiazepine, most notably producing a somewhat faster recovery time.…”
Section: Discussionsupporting
confidence: 50%
“…First‐aid procedures and administration of medications are adjusted depending on the age and physical development of the child. In the younger age group, ( < 12 year of age) anxiety and dental phobia are more pronounced as risk factors for emergencies. Treatment under general anaesthesia or under intravenous or inhalation sedation can contribute to an emergency situation in the dental office.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the need and demand for sedation in the United States and other countries (2,7,9,22). Tools to evaluate the need for sedation in individual patients are available, but they do not address the demands of the patient (23,24).…”
mentioning
confidence: 98%